2006
DOI: 10.1007/s11104-005-7931-4
|View full text |Cite
|
Sign up to set email alerts
|

Boron Increases Synthesis of Glutathione in Sunflower Plants Subjected to Aluminum Stress

Abstract: Ionic stress caused by high aluminum (Al) concentrations is one of the most widespread phytotoxicity problems globally in agricultural regions, greatly limiting crop yield in affected areas. The objective of this work was to examine a possible involvement of boron (B) in the detoxification of Al by stimulating glutathione (GSH) metabolism, a mechanism essential for the resistance of plants under stress conditions. Our results clearly demonstrate that increased application of B in the presence of high Al concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 31 publications
(28 reference statements)
2
23
0
1
Order By: Relevance
“…Espessura da casca da maçã e produção de sementes (f) por plantas de algodão em resposta às concentrações de boro e zinco na solução nutritiva Isto pode estar associado às estratégias que as plantas utilizam para se desenvolverem em substratos com baixas e altas concentrações de B que consistem, basicamente, no efluxo de B, metabolismo antioxidante e deposição de lignina e suberina na raiz (Ruiz et al 2006;Cervilla et al 2009a,b). A EUB foi influenciada positivamente pelo aumento da concentração de B em 0 µM L -1 de Zn até a concentração de 40 µM L -1 de B e 2 µM L -1 de Zn, havendo efeito negativo nas concentrações mais elevadas dos nutrientes (Figura 4C).…”
Section: Figure 1 Plant Height (A) Stem Diameter (B) Number Of Reprunclassified
“…Espessura da casca da maçã e produção de sementes (f) por plantas de algodão em resposta às concentrações de boro e zinco na solução nutritiva Isto pode estar associado às estratégias que as plantas utilizam para se desenvolverem em substratos com baixas e altas concentrações de B que consistem, basicamente, no efluxo de B, metabolismo antioxidante e deposição de lignina e suberina na raiz (Ruiz et al 2006;Cervilla et al 2009a,b). A EUB foi influenciada positivamente pelo aumento da concentração de B em 0 µM L -1 de Zn até a concentração de 40 µM L -1 de B e 2 µM L -1 de Zn, havendo efeito negativo nas concentrações mais elevadas dos nutrientes (Figura 4C).…”
Section: Figure 1 Plant Height (A) Stem Diameter (B) Number Of Reprunclassified
“…It has been reported that B supply under Al stress could increase and stimulate antioxidant activities, thereby, alleviates the Al-induced inhibition of root elongation (Lukaszewski and Blevins 1996). Ruiz et al (2006) reported that increased application of B stimulates GSH biosynthesis (antioxidant) in response to high Al concentration in the growth medium, the activation of the defense system could reduce oxidative stress, and reduce phytotoxicity induced by Al toxicity. We found that 25 µM B resulted in the higher activities of antioxidant enzymes (POD, CAT, and APX) to cut down membranes lipid peroxidation by lowering hydrogen peroxide (H 2 O 2 ) contents produced by Al toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…So this complex network of cells makes the cell wall tighter and hinders the entrance of Al into the cell, thus preventing Al contact with cell organelles (O'Neill et al 2004;Corrales et al 2008). Amelioration of Al toxicity by using B has been stated by many researchers in squash (LeNoble et al 1996b), alfalfa (LeNoble et al 1996a), sour pummel (Jiang et al 2009), pea (Yu et al 2009), sunflower (Ruiz et al 2006), common bean (Stass et al 2007), rapeseed (Yan et al 2018), trifoliate (Riaz et al 2018a(Riaz et al , 2018b and however, such an effect was not found by Wang et al (2005) in maize. Many reports have indicated the mechanism behind B-induced alleviation of Al-toxicity, yet the actual mechanism has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that loss the integrity of cell membrane at low concentration of boron stimulates the accumulation of phenolic and their oxidation products (Cakmak &Römheld, 1997 andKobayashi et al, 2004). Under aluminum stress, boron encourage the accumulation of glutathione levels in sunflower and maize plants (Ruiz et al, 2006) and gradually support and stimulates the antioxidant (Corrales et al, 2008).…”
Section: Secondary Metabolism and Oxidative Stressmentioning
confidence: 99%